1992
DOI: 10.1128/mcb.12.11.4988
|View full text |Cite
|
Sign up to set email alerts
|

Genome rearrangement in top3 mutants of Saccharomyces cerevisiae requires a functional RAD1 excision repair gene.

Abstract: Saccharomyces cerevisiu cells that are mutated at TOP3, a gene that encodes a protein homologous to bacterial type I topoisomerases, have a variety of defects, including reduced growth rate, altered gene expression, blocked sporulation, and elevated rates of mitotic recombination at several loci. The rate of ectopic recombination between two unlinked, homeologous loci, SAMI and SAM2, is sixfold higher in cells containing a top3 null mutation than in wild-type cells. Mutations in either of the two other known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 16 publications
3
34
0
Order By: Relevance
“…The sam1-⌬BglII frameshift and sam1:: LEU2 deletion/disruption mutations were constructed and used as previously described (3)(4)(5). The sam2-⌬SalI::HIS3 and sam2-⌬SalI::CYH2::URA3 gene disruption constructions described above were transplaced into the yeast genome by single-step gene disruption (33).…”
Section: Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sam1-⌬BglII frameshift and sam1:: LEU2 deletion/disruption mutations were constructed and used as previously described (3)(4)(5). The sam2-⌬SalI::HIS3 and sam2-⌬SalI::CYH2::URA3 gene disruption constructions described above were transplaced into the yeast genome by single-step gene disruption (33).…”
Section: Strainsmentioning
confidence: 99%
“…AdoMet prototrophs can arise as the result of several different events. In addition to recombination between the SAM substrate fragment on the plasmid and the SAM2 locus, gene conversion between the SAM1 and SAM2 loci, as well as spontaneous reversion of the mutations at either of the SAM loci, can result in AdoMet prototrophy (3)(4)(5). The opposite orientations of the SAM1 and SAM2 genes relative to their centromeres preclude the isolation of reciprocal recombinants (5).…”
Section: Strainsmentioning
confidence: 99%
“…Determining the nature of the event that resulted in AdoMet prototrophy requires digesting the DNA with enzymes that give diagnostic fragments if the insertions that inactivate the SAM genes are replaced with wild-type information (5,6). Coconversion events are documented by digesting DNA from the recombinants with PvuII before blotting and hybridization ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Sgs1 and Top3-Rmi1 were shown to have interdependent and independent functions in meiosis (Kaur et al 2015;Tang et al 2015). However an antirecombination role for the Top3-Rmi1 complex has not been clearly established, though previous studies showed that top3D mutants increased recombination between divergent DNA sequences (Wallis et al 1989;Bailis et al 1992).…”
mentioning
confidence: 97%